15 minutes of fame : the dark underbelly of celebrity - Elelman, Susie; Morris, Julia (Chatswood, NSW : New Holland Publishers, 2018)
A funny witty read on the " behind the scenes" of making it to world of showbusiness. The players behind the scenes after a 40 year career in Australia show business. The media is a ravenous beast, chewing up talent and disposing of careers on a daily basis. Along the way there are many hurdles to navigate ... nepotism, favouritism, sexism, harassment, incompetence. The list is endless. How then do you not only earn your 15 minutes of fame, make the most of it and turn it into a career? Broadcaster Susie Elelman has done it all ... beauty queen, radio host, TV star, charity champion, humanitarian and accomplished author (Half My Size, 2018). In her new book, she outlines the many pitfalls people in the media face in their careers, using her own experience as anecdotes while also including various 'amalgams' of anonymous posers, prancers, actors, divas, backstabbers, starlets, serial pests and harassers that permeate each level of the media. Hilarious, poignant, insightful, informative and more real than reality TV, '15 Minutes of Fame' is sure to blow the lid off the fame game that has been played out in the media over the past thirty years and provide a valuable template for anyone considering a career in the spotlight.
Keywords: Elelman, Susie; Women television personalities -- Australia -- Biography; Television personalities -- Australia -- Biography; Television talk show hosts -- Australia -- Biography; Television personalities; Television talk show hosts; Television talk shows; Women television personalities; Australia; Autobiographies; Autobiographies; Biography